Formulasi Sabun Transparan Berbahan Dasar Minyak Kelapa dengan Penambahan Ekstrak Buah Pepaya dan Scrub Kunyit - Andrew Setiawan Rusdianto; Shanya Widyan Firdaus; Andi Eko Wiyono (Pro-Life, 2024)
Soap is one of the cosmetic products used daily that continues to undergo development by adding organic and inorganic ingredients that contain supporting ingredients according to their function. The potential of papaya and turmeric fruit is combined to make transparent, solid soap with the addition of fruit extract and scrub. Papaya fruit contains vitamin C, which functions as an antioxidant and can be beneficial for reducing free radicals that can damage skin DNA. Turmeric also contains fiber, which functions as an abrasive to remove dead cells from the skin and does not cause irritation. This research aims to determine an effective formulation for making transparent soap based on coconut oil with the addition of papaya extract and turmeric scrub. This study used a completely randomized design consisting of two factors, six treatments, and three replications. The parameters used are organoleptic, water content, degree of acidity (pH), ethanol-insoluble ingredients, free fatty acids, vitamin C content, foam stability, and hardness. Based on research that has been carried out, the addition of papaya vitamin C extract and turmeric scrub affects water content, free fatty acids, vitamin C content, foam hardness and stability, as well as the organoleptic color, aroma, transparency, and overall acceptability of the soap preparation. The characteristics of the ethanol-insoluble material and the pH value were only influenced by papaya vitamin C extract. The best transparent soap treatment based on the de Garmo method effectiveness index test is the A3B1 treatment.